Социально-экономическая модернизация как системная трансформация (Путеводитель предпринимателя, 2020)
This article reveals new meaning and content of «modernisation» (upgrade) definition, directions of its evolution and their influence on upgrading practices, including quality and quantity factors and contemporary state of economy characteristics. The article also manifests author point ofview concerning «modernisation» (upgrade) strategy for Russian economy.